An Analysis of Undergraduate Students’ Ability and Their Difficulties in Identifying Simple, Compound, Complex, and Compound-Complex Sentences - Surya Maulana; Yuli Markhamah; Ahmad Jailani (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2024)
This paper discusses the result of analyzing the ability of undergraduate students to the difficulty of identifying simple sentences, compound sentences, complex sentences, and compound-complex sentences. A descriptive quantitative approach and a descriptive qualitative approach were used in this study. Descriptive quantitative was used to see the student score test in analyzing simple sentences, compound sentences, complex sentences, and compound-complex sentences. Descriptive qualitative was used to see the result of students’ interviews on their difficulty identifying simple, compound, complex, and compound-complex sentences. This study shows that students' ability mean score was 11.84 from 20 points, the median was 12 from 20 points, and the range was 6 (as a lower score) and 17 (the highest score) from 20 points. Most of the students still have difficulty identifying the formation of simple sentences, compound sentences, complex sentences, and compound-complex sentences. Mainly because they still don’t understand connectors in the four types of sentences, such as subordinate connectors. Therefore students are required to practice writing in order to make it easier to form a simple sentences, compound sentences, complex sentences, and compound-complex sentences.